Prosperity level and fishermen income at Sadeng Beach fishery port, Gunung Kidul regency (Research, Society and Development, 2020)
Poverty is the main factor triggering the high level of exploitation of fisheries resources. Prosperity of fishermen becomes primary key in fisheries development. Fisherman income level is primary factor in improving fishermen prosperity. The existence of a famine season is primary fishermen problem in fulfill the main needs. Because of it, this research is done with the purpose to see the fishermen income level in fish season, famine season and the average income of fishermen to determine the level of welfare of fishermen based on the type of boat used. The method is using fisheries business analysis, fishermen welfare level based on the Indonesian Central Statistics Agency criteria descriptive analysis. The basic method used in this research is descriptive analysis, business analysis of fisheries, the level of welfare of fishermen based on the criteria of the Indonesian Central Statistics Agency. The results is the greater boat type, welfare level and income will increase, but the economic sustainability is lower because larger ship, loss risk, time and distance to sea also increases so that influence of the famine season will be greater, the average income of fishermen is above the regional minimum wage and the welfare level of fishermen is included in the moderate or well-being category. Thus, to increase the income and welfare of fishermen, it is necessary to increase education levels, subsidized housing programs, alternative work and increase boat type may be done if there is capital support and guarantees from the government.